Sistem Informasi Produksi Barang Pada PT ABC - Rusmawan, Uus (Fakultas Teknik, Universitas Bhayangkara Jakarta Raya, 2020)
This study discusses the manufacture of goods production applications in manufacturing companies. Problems that arise include the difficulty of obtaining information relating to the process of production of goods from the purchase of raw materials, the use of raw materials for production, sale of finished goods and information on stock of raw materials for production and finished goods. One of the main objectives of this study is to overcome the deficiencies mentioned above in terms of presenting information and reporting the production process of goods. This research method uses waterfall. The results of research in the form of application of the production of goods provide one alternative solution to the availability of information systems for the production of goods for interested parties